Leveraging Professional Sports Teams to Encourage Healthy Behavior: A Review of 4 Years of Calgary Flames Health Training Camp Events - Ori, Elaine M.; Berry, Tanya R.; McCormack, Gavin R.; Brett, Kelly R.; Lambros, George A.; Ghali, William A. (Frontiers in Public Health, 2020)
Professional sporting teams may be well-positioned to act as promoters of health behaviors given their fixture within a community, and association with physical activity, nutrition, and other healthy behaviors. Over 4 years, the Calgary Flames Sport and Entertainment Corporation in conjunction with local health promotion professionals, delivered a health promotion event to the public, The Calgary Flames Health Training Camp (FHTC) in Calgary, Alberta, Canada. The purpose of these annual events has been to inspire and encourage healthy behavior uptake and adherence. A description of the FHTC over each of 4 years (2015–2018), lessons learned, and some evaluative work done alongside the event on 2 of the 4 years. In 2017, self-report surveys were administered to event attendees to assess current health status including physical activity, socio-cognitive variables, health information preference, and intention to make healthful behavior change based on event attendance. Biometric data was collected including blood pressure, height, weight, and resting heart rate. Evaluations of the four consecutive events showed that the Calgary Flames Sport and Entertainment Corporation has an ability to attract substantial numbers of the general public to attend FHTC events. Self-report measures from 2017 suggest that already-active populations may be most interested in attending however, the events do appear to inspire attendees to consider behavioral changes for health. The events helped to identify individuals with health risks requiring medical attention but has not yet resulted in known behavior changes. Positive community health impacts may arise from collaboration between health promoters and professional sporting organizations.